Incidencia de cáncer de tiroides en la provincia de Neuquén, período 2001-2012 - Cohen Sabban, Juan Manuel; Palmero, Cinthia Ariadna; Bertrand, Beatriz; Aiello, Ana; Ghiglioni, Amalia; Mac Donell, Marica Celina; Croci, Cecilia; Caballeiro, Patricia; Juvenal, Guillermo Juan (Elsevier, 2014)
Fil: Cohen Sabban, Juan Manuel. Sociedad de Endocrinología de Neuquén y Rio Negro; Argentina